Peran Pondok Pesantren dalam Pembentukan Karakter Santri dalam Manajemen Pendidikan Islam - Firyal Rafidah Lesmana; Hanun Salsabilah; Beta Alviana Febrianti (CV. Syntax Corporation Indonesia, 2021)
The background of this research is the decline of moral values in the lives of teenagers in the current era of globalization. This study aims to determine how the role or the Aisyiyah Islamic boarding school in shaping the character of students in Islamic education management. The research method used in this study is a qualitative research with a licterature study approach (Library Research). Data collection techniques in this study by conducting online interviews through the Whatsapp application and data collection is also supported by literature studies with the help of various available materials such as books and journals. The findings of this study, namely: 1) planning for the formation of character education is prepared in accordance with the vision, mission and educational objectives of curriculum development, methods and socialization involving PPRU stakeholders, 2) organizing with the main person in charge, namely islamic boarding schoolls, and caregivers students, 3) character education is carried out in a formal, informal and non-formal way, 4) control can be carried out by all PPRU stakeholders through schooll reports, boarding reports, and dorm reports which can determine the increase and graduation of students.